Circulating microRNA signatures as potential biomarkers differentiating diabetic, prediabetic, and healthy individuals - Abu-Toamih Atamni, Hanifa J.; Shapira, Guy; Ortenberg, Rona; Sultan, Maya; Twito, Orit; Yoseph-Barzilay, Liat; Shomron, Noam; Rashid, Gloria (Frontiers in Endocrinology, 2025)
IntroductionCirculating microRNAs (miRNAs) are small non-coding RNAs that regulate gene expression and play key roles in metabolic diseases, including diabetes. This study aimed to identify circulating miRNA signatures linked to glycemic status, vitamin D deficiency, aspirin consumption, and platelet activity in individuals with type 2 diabetes, prediabetes, and healthy controls.MethodsPlasma samples from 24 participants (14 with diabetes, 2 prediabetic, and 8 non-diabetic controls) were analyzed using next-generation sequencing to assess differences in miRNA expression.ResultsAlthough principal component analysis showed no group separation, pairwise testing identified 131 miRNAs that were significantly altered between the diabetic and control groups, as well as 141 miRNAs between the prediabetic and control groups (FDR <0.05), with 56 overlapping between contrasts. Fourteen miRNAs in the pre-diabetic group and twelve in the diabetic group overlapped with literature-supported candidates, reinforcing their clinical relevance. In the direct diabetes vs. prediabetes comparison, no miRNAs passed FDR. Still, consistent trend-level decreases in diabetes were observed for hsa-miR-4776-5p, hsa-miR-6778-3p, and hsa-miR-5002-3p, which were among the most upregulated in prediabetes vs. controls. Sex-stratified analyses revealed distinct miRNA expression patterns, emphasizing the influence of biological sex on miRNA regulation in glucose metabolism. Correlation analyses highlighted miRNAs associated with glucose/HbA1c, alongside relationships among vitamin D status, glycemia, and platelet function.DiscussionCollectively, these data highlight the exploratory potential of circulating miRNAs as candidate early biomarkers for glycemic dysregulation, providing a foundation for future validation and development of improved diagnostic and preventive strategies for type 2 diabetes.